Association of high fibrinogen to albumin ratio with long-term mortality in patients with spontaneous intracerebral hemorrhage - Chen, Shiping; Zhang, Yu; Xiao, Yangchun; Cheng, Xin; Peng, Liyuan; Tian, Yixin; Li, Tiangui; He, Jialing; Hao, Pengfei; Chong, Weelic; Hai, Yang; You, Chao; et al. (Frontiers in Neurology, 2024)
Background The association between fibrinogen-to-albumin ratio (FAR) and in-hospital mortality in patients with spontaneous intracerebral hemorrhage (ICH) has been established. However, the association with long-term mortality in spontaneous ICH remains unclear. This study aims to investigate the association between FAR and long-term mortality in these patients. Methods Our retrospective study involved 3,538 patients who were diagnosed with ICH at West China Hospital, Sichuan University. All serum fibrinogen and serum albumin samples were collected within 24 h of admission and participants were divided into two groups according to the FAR. We conducted a Cox proportional hazard analysis to evaluate the association between FAR and long-term mortality. Results Out of a total of 3,538 patients, 364 individuals (10.3%) experienced in-hospital mortality, and 750 patients (21.2%) succumbed within one year. The adjusted hazard ratios (HR) showed significant associations with in-hospital mortality (HR 1.61, 95% CI 1.31–1.99), 1-year mortality (HR 1.45, 95% CI 1.25–1.67), and long-term mortality (HR 1.45, 95% CI 1.28–1.64). Notably, the HR for long-term mortality remained statistically significant at 1.47 (95% CI, 1.15–1.88) even after excluding patients with 1-year mortality. Conclusion A high admission FAR was significantly correlated with an elevated HR for long-term mortality in patients with ICH. The combined assessment of the ICH score and FAR at admission showed higher predictive accuracy for long-term mortality than using the ICH score in isolation.